Flipped Learning as Pedagogical Innovation: A Community Engagement Initiative In Pre-Service Language Teacher Education - Oya, Abas; Arwan, Arwan; Haris, Abdul; Bagus, Muhammad Fadli (STKI Harapan Bima, 2025)
This community service activity aimed to introduce Flipped Learning as an innovative instructional model to first-semester students of the Indonesian Language and Literature Education Study Program at STKIP Harapan Bima. The main issue addressed was the limited prior understanding of 21st-century teaching approaches, particularly strategies that position learners as active participants. The program was implemented through an on-site public lecture involving 50 student participants, featuring an academic expert as the main speaker and supported by institutional leaders as keynote contributors. The activity consisted of four stages: material preparation and coordination, lecture implementation, student reflection facilitation, and closing with documentation. The results indicated strong student engagement and increased awareness of the conceptual distinctions between conventional and flipped models. Participants demonstrated a growing understanding of the pedagogical shift needed in language and literature instruction. Further discussion revealed that the lecture not only broadened theoretical knowledge but also fostered reflective awareness of the educator’s role in modern classrooms. This initiative marks a foundational step toward integrating student-centered learning approaches early in teacher education programs.